SYSTEMS AND METHODS FOR TOOTH SEGMENTATION (2021)
A method and a system for determining an orthodontic treatment for a plurality of teeth of a subject are provided. The method comprises: receiving a 3D representation of a first tooth and a second tooth, adjacent thereto, of the subject, of a plurality of teeth of the subject; obtaining a tooth-gingiva segmentation loop; identifying an outer set of vertices positioned outside the tooth-gingiva segmentation loop and an inner set of vertices positioned inside the tooth-gingiva segmentation loop; generating a first interdental loop extending, along the 3D representation, through a given inner vertex and a given outer vertex, such that: the first interdental loop is at least partially indicative of an interdental boundary between the first tooth and the second tooth; and the first interdental loop intersects the tooth-gingiva segmentation loop; and generating the first tooth 3D representation based on the tooth-gingiva segmentation loop and the first interdental loop.